Law No. 32 of 2009 concerning PPLH as an Instrument for Limiting the Utilization of Natural Resources from the Perspective of Maqāṣid al-Syari’ah - Upi Sopiah Ahmad (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
The use of natural resources in development practices often raises issues of pollution and environmental damage when legal restrictions are understood solely procedurally and administratively. Law Number 32 of 2009 concerning Environmental Protection and Management places environmental planning as the foundation of management, particularly through the provisions in Article 10. However, this provision is still often read in a formalistic manner so that its normative function as an instrument for limiting the use of natural resources has not been optimized. This article aims to analyze the position of Article 10 of Law No. 32 of 2009 from the perspective of maqāṣid al-syarī'ah, with an emphasis on the principle of preventing damage (dar' al-mafāsid), in order to emphasize the orientation of environmental protection and human safety. This study uses a normative legal research method with a statutory and conceptual approach. The primary legal material in the form of Law No. 32 of 2009, especially Article 10, is reviewed together with relevant Islamic legal sources, and supported by maqāṣid literature and contemporary environmental law studies as secondary legal materials. The research results show that Article 10 not only functions as an administrative planning norm, but also contains preventive content that aligns with the objectives of the maqāṣid al-syarī'ah, particularly the protection of life and the public welfare. Thus, Article 10 can be positioned as a normative meeting point between national environmental law and the basic principles of Islamic law in limiting the sustainable use of natural resources.